Comparison of Two Fuzzification Algorithms (EC-pH and EC-pH Error Error Difference Fuzzifications) of Nutrient Solution Control in Plant Factory - Ardiansyah, Ardiansyah; Aji, Bastian Seno; Sumarni, Eni (The University of Lampung, 2024)
Plant factory is a model of intensive indoor cultivation with microclimate conditioning and lighting. This research aims to develop a fuzzy-based control and monitoring system for TDS, pH, and EC parameters in hydroponic integrated with Internet of Things (IoT) technology. The research was conducted at the Laboratory of Bio-environmental Management and Control Engineering, Department of Agricultural Technology, Faculty of Agriculture, Universitas Jenderal Soedirman. The research results showed that the monitoring and control system using the Fuzzy control algorithm with EC and pH fuzzification and the Fuzzy control algorithm with error and error difference fuzzification were successfully implemented. The data obtained indicated that the Fuzzy control algorithm with error and error difference fuzzification performed better in terms of accuracy and energy efficiency. The Fuzzy control algorithm with error and delta error difference fuzzification was more accurate because a single set pint value used as a reference resulted in better control, and this algorithm also consumed less energy than the Fuzzy control algorithm with EC and pH fuzzification, with a difference of 30 minutes in EC control and 5 minutes in pH control. Keywords: AB Mix Nutrient, Arduino, ESP8266, Fuzzy Logic Controller, Plant Factory.